Judi Online : Faktor Pemicu Perceraian Dalam Keluarga Modern - Fadillah Utami; Siti Patimah; Adenan Adenan; Darwis Mustakim (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Online gambling has increasingly become a major social issue, particularly in the context of family and marital stability. This study aims to explore and analyze the impact of online gambling addiction on marital relationships, with a focus on the causes leading to divorce. Employing a qualitative research approach, data were gathered through in-depth interviews with individuals and couples who had experienced divorce as a direct consequence of one partner’s online gambling behavior. The results of this study reveal that online gambling addiction significantly contributes to financial instability, emotional distance, repeated conflicts, and the eventual breakdown of communication and trust within the relationship. Many participants reported experiencing feelings of betrayal, frustration, and emotional exhaustion due to the compulsive gambling behavior of their partners. In several cases, gambling debts resulted in the sale of family assets and prolonged financial insecurity, which further strained the relationship. Moreover, the secrecy surrounding gambling activities often led to the erosion of mutual respect and transparency between spouses. This research underscores the urgent need for public education and policy intervention to mitigate the negative effects of online gambling on families. Support systems such as counseling, rehabilitation programs, and financial planning services are crucial to help affected individuals recover and rebuild their lives. By shedding light on the destructive nature of online gambling on family dynamics, this study aims to contribute to the broader discourse on mental health, addiction, and the preservation of marital stability in the digital age.